A risk-based approach towards infringement prevention on the internet: adopting the anti-money laundering framework to online platforms. (27th July 2018) - Ullrich, Carsten
Abstract: This article suggests a new approach towards online service provider liability which relies on duty of care. It proposes a concrete compliance framework for online platforms, borrowed from risk regulation, and modelled on anti-money laundering (AML) obligations in the financial sector. First, the prohibition on obliging platforms to monitor content in a general manner under the E-Commerce Directive will be discussed. On the face of it this may clash with a standardized requirement to filter for infringing content. Subsequently, the regulatory choice for such a duty of care standard will be explored. It is argued that the largely self-regulatory proposals currently on the table may be ill fitted to achieve traction and accountability. Finally, a three-tier compliance framework, modelled on the AML system and using a risk-based approach, is proposed. The pitfalls of such a highly automated compliance solution, which enforces complex legal norms, will also be touched on.